Strategi Komunikasi Pemasaran dalam Membangun Loyalitas Pelanggan Pada Bisnis Nail Art Nailedshape - Gracia Marsella Nggay; Sahri Aflah Ramadiansyah (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
This study examines the implementation of Integrated Marketing Communication (IMC) at NailedShape, a Bali-based nail art micro-enterprise, as a strategy to foster customer loyalty. NailedShape operates under a home-service and home studio model, primarily using Instagram for promotion and customer engagement. The study utilizes a descriptive qualitative method, collecting data through interviews and observations with the owner, customers, and micro-influencers. The research findings show that NailedShape successfully employs IMC techniques, such as visual content, customer testimonials, and collaborations with digital influencers, to capture attention and create strong emotional connections with customers. This integrated approach helps in building a positive brand image and maintaining customer engagement. However, the study also highlights challenges, such as limited resources and frequent changes to social media algorithms, which hinder consistent communication and marketing efforts. Despite these obstacles, the study concludes that a well-executed IMC strategy remains effective in enhancing customer loyalty, reinforcing the importance of an integrated communication approach for small and medium enterprises (SMEs) in the beauty industry. By utilizing digital platforms effectively, NailedShape can compete in a highly dynamic market. The findings suggest that beauty-based MSMEs can benefit greatly from IMC in the digital era, as it not only enhances brand perception but also helps in building lasting customer relationships.